Theoretical analysis of coupling between laser diodes and conically lensed single-mode fibres utilising ABCD matrix method - Rahman,, FA; Teik,, CH; Takahashi,, K (2003)
In this paper, we present a simple technique to determine the coupling efficiency between a laser diode and a conically lensed fibre, based on the ABCD transformation matrix method. In the analysis we have also taken into account the effect of multiple reflection between the laser facet and lens surface. The calculated results were compared for conical microlens etched at different times to see the power variation difference. We have also compared our analysis technique to that of previous work and we have found that the present method is reliable in predicting the coupling efficiency of conical microlens. (C) 2002 Elsevier Science B.V. All rights reserved.